Factor Analysis of Innovative Work Behavior in IT Employees with Millennial Generation Characteristics - Arini, Dewi Ulfah; Hardani, Hardani; Rusmalia, Rusmalia (Syntax Corporation, 2024)
This study aims to analyze the factors that influence innovative work behavior in IT employees with millennial generation characteristics. The millennial generation is known as a group that is adaptive to technology and has great potential to generate innovative ideas in the work environment. In the era of growing digitalization, the innovative ability of IT employees is crucial for companies to compete effectively. This research uses a quantitative approach with a survey method involving IT employees aged 23-38 years as respondents. The data collected was analyzed using factor analysis techniques to identify the main variables that contribute to innovative work behavior. The results showed that factors such as intrinsic motivation, supportive work environment, transformational leadership, and innovative organizational culture have a significant influence on the innovative work behavior of millennial generation IT employees. The findings are expected to contribute to companies in developing appropriate strategies to increase innovative work behavior among IT employees, especially the millennial generation, to support the sustainability of innovation in the organization.